The Dresden Protocol for Multidimensional Walking Assessment (DMWA) in Clinical Practice - Trentzsch, Katrin; Weidemann, Marie Luise; Torp, Charlotte; Inojosa, Hernan; Scholz, Maria; Haase, Rocco; Schriefer, Dirk; Akgün, Katja; Ziemssen, Tjalf (Frontiers in Neuroscience, 2020)
Walking impairments represent one of the most debilitating symptom areas for people with multiple sclerosis (MS). It is important to detect even slightest walking impairments in order to start and optimize necessary interventions in time to counteract further progression of the disability. For this reason, a regular monitoring through gait analysis is highly necessary. At advanced stages of MS with significant walking impairment, this assessment is also necessary to optimize symptomatic treatment, choose the most suitable walking aid and plan individualized rehabilitation. In clinical practice, walking impairment is only assessed at higher levels of the disease using e.g. the Expanded Disability Status Scale (EDSS). In contrast to the EDSS, standardized functional tests such as walking speed, walking endurance and balance as well as walking quality and gait-related patient-reported outcomes allow a more holistic and sensitive assessment of walking impairment. In recent years, the MS Center Dresden has established a standardized monitoring procedure for the routine multidimensional assessment of gait and balance disorders. In the following protocol we present the techniques and procedures for the gait and balance analysis of people with MS at the MS Center Dresden. Patients are assessed with a multidimensional gait analysis at least once a year. This enables long-term monitoring of the walking impairment, which allows early active intervention regarding further progression of disease and improves the current standard clinical practice.